A qualitative evaluation of the use of interventions to treat fatigue among cancer survivors: A healthcare provider's view. (15th November 2020) - Martin, Elise; Zingarello, Anna; Di Meglio, Antonio; Baciarello, Giulia; Matias, Margarida; Charles, Cécile; Arvis, Johanna; Dumas, Agnès; Menvielle, Gwenn; Vaz‐Luis, Ines
Abstract: Objective: Cancer‐related fatigue (CRF) is among the most common and distressing side effects of cancer treatment. Different types of interventions, including physical activity (PA), psychosocial and mind–body interventions, have been shown to reduce CRF. We aimed to explore HCPs' practices and barriers to refer patients towards interventions to reduce CRF. Methods: We performed a qualitative study using key informant interviews among a sample of 20 HCPs including medical, surgical and radiation oncologists, pain specialists, nurses, psychologists, psychiatrists and physiotherapists recruited from breast, prostate and colorectal cancer disease groups from a comprehensive cancer centre. Results: Most interviewees reported not to address CRF spontaneously during consultations. When the topic of CRF was brought up by patients, all interviewees acknowledged to recommend PA, whereas few would recommend psychosocial or mind–body interventions. Barriers to recommend interventions to manage CRF included: lack of knowledge about CRF and its treatment, lack of time and complexity of the referral due to their accessibility and cost. Conclusion: In a diverse sample of HCPs, most acknowledged not to address CRF proactively with their patients, but identified several actionable barriers. Specific training on screening and management of CRF and improving the referral network dedicated to interventions need to be implemented.